A QUALITATIVE CASE STUDY ON THE LEGACY OF COLONIALISM IN EDUCATION: CONFRONTING PAST AND PRESENT INFLUENCES - Mbanjwa, Sibonelo Thanda (Student's Journal of Health Research Africa, 2025)
The decolonization of South African universities is a critical movement to dismantle colonial legacies that continue to shape higher education. Despite efforts to redefine curricula, institutional cultures often marginalize indigenous knowledge systems. This study examines the gaps in current decolonization initiatives and advocates for systemic transformation that integrates African epistemologies into teaching, research, and community engagement. A qualitative research design was employed, incorporating policy analysis, stakeholder interviews, and case studies across three universities in KwaZulu-Natal: Mangosuthu University of Technology (MUT), Durban University of Technology (DUT), and the University of KwaZulu-Natal (UKZN). 450 participants were surveyed to assess perspectives on decolonization and institutional responses. Findings indicate varying levels of support for decolonization efforts: at MUT, 30% strongly support, 35% support, 20% are neutral, 10% oppose, and 5% strongly oppose; at DUT, 40% strongly support, 30% support, 15% are neutral, 10% oppose, and 5% strongly oppose; at UKZN, 45% strongly support, 25% support, 15% are neutral, 10% oppose, and 5% strongly oppose. Key strategies identified for meaningful transformation include Indigenous student recruitment and retention, curriculum redesign centered on African epistemologies, and partnerships with local communities to co-create knowledge. While there is strong support for decolonization, resistance remains a challenge. Addressing this requires institutional commitment, inclusive policymaking, and sustained engagement with indigenous knowledge holders. Universities must embed decolonization principles within their frameworks by implementing curriculum reforms, strengthening community collaborations, and fostering policies that prioritize African scholarship. This study contributes to the ongoing discourse on educational transformation in South Africa, offering practical strategies for systemic change.